2003
DOI: 10.2190/feal-12yh-31g7-nwh5
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Group Dynamics in a Brief Motivational Intervention for College Student Drinkers

Abstract: Previous research indicates that brief motivational interventions for college student drinkers may be less effective in group settings than individual settings. Social psychological theories about counterproductive group dynamics may partially explain this finding. The present study examined potential problems with group motivational interventions by comparing outcomes from a standard group motivational intervention (SGMI; n = 25), an enhanced group motivational intervention (EGMI; n = 27) designed to suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In one study, examining members' appraisals of self-help groups (i.e., Multiple Sclerosis, Compassionate Friends, and Overeaters Anonymous groups), members who perceived that their group was well organized and had a proficient leader reported greater satisfaction with the group, higher levels of selfγesteem, and lower levels of depression (Maton, 1988). Similar findings have been obtained in other studies, which have shown that primary group outcomes are related to several features of group environments, including perceived levels of group cohesion (Budman, Soldz, Demby, Feldstein, Springer & Davis, 1989;Meredith, 1987), disruptive group dynamics (Faris & Brown, 2003), group leadership and implementation (Kulic, Horne, & Dagley, 2004), and perceived group climate (Choi, Price, & Vinokur, 2003;MacKenzie, Dies, Coché, Rutan, & Stone, 1987).…”
supporting
confidence: 71%
“…In one study, examining members' appraisals of self-help groups (i.e., Multiple Sclerosis, Compassionate Friends, and Overeaters Anonymous groups), members who perceived that their group was well organized and had a proficient leader reported greater satisfaction with the group, higher levels of selfγesteem, and lower levels of depression (Maton, 1988). Similar findings have been obtained in other studies, which have shown that primary group outcomes are related to several features of group environments, including perceived levels of group cohesion (Budman, Soldz, Demby, Feldstein, Springer & Davis, 1989;Meredith, 1987), disruptive group dynamics (Faris & Brown, 2003), group leadership and implementation (Kulic, Horne, & Dagley, 2004), and perceived group climate (Choi, Price, & Vinokur, 2003;MacKenzie, Dies, Coché, Rutan, & Stone, 1987).…”
supporting
confidence: 71%
“…This can be accomplished via appropriate statistical analyses of observational and/or experimental data that might be available to the analyst. In empirical studies of groups, response data is sampled from individual group members, and thus, it is hierarchical in nature, as pointed out by (Nezlek & Zyzniewski, 1998) and others (e.g., see (Anderson & Ager, 1978), (Draper, 1995), (Faris & Brown, 2003), (Forsyth, 1998), (Hoyle & Crawford, 1994), (Hoyle, Georgesen, & Webster, 2001), (Kenny & Voie, 1985), (Quillian, 1995), (Raudenbush, 1995), (Raudenbush & Willms, 1995)). For example, one might be interested in determining the effect of a host population's unemployment rate and skill level of individuals on the individual or collective attitudes and behaviors towards immigrants.…”
Section: Discussionmentioning
confidence: 99%